Application of sustainability indicators for the evaluation and selection of robust organic-rich wastewater treatment technology for resource recovery - Chrisogoni Paschal; Mwemezi J. Rwiza; Karoli N. Njau (AIMS Bioengineering)
A comparative study was conducted to compare the performance of waste stabilization ponds (WSPs) with an upflow operation type advanced facultative pond integrated with constructed wetland (AFP-CW) technologies. Our aim was to address gaps in economic, environmental, and social aspects identified in traditional WSPs. Economic, environmental, and social sustainability indicators were used in a mathematical model to select a sustainable technology for organic-rich wastewater treatment for resource recovery. The results showed that for the AFP-CW, economic, environmental, and social indicators were weighted at 10.18%, 51.11%, and 38.71%, respectively, while for WSPs, the percentages were 14.55, 48.39, and 37.06, respectively. The composite sustainability indicator (CSI) for AFP-CW was 42.14% and for WSPs was 39.27%, with the global sustainability indicator (GSi) reaching 21.54% for AFP-CW and 18.88% for WSPs. A sensitivity analysis revealed that the maximum global sustainability indicator was 22.34% for AFP-CW and 19.54% for WSPs. Overall, the AFP-CW was considered a more sustainable technology for wastewater treatment, with lower economic but higher environmental and social sustainability indicators compared to WSPs, which showed higher economic but lower environmental and social sustainability indicators. The sustainability of AFP-CW is supported by its small construction area, nutrient recovery in sludge, biogas recovery, reduced global warming impact, as well as nutrient and water recycling for irrigation.